Donors of effective genes for scald resistance in barley - G. S. Konovalova; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. One of the most harmful diseases of barley in all areas of its cultivation is scald. The causal agent Rhynchosporium commune Zaffarano, B.A. McDonald & A. Linde (formerly – Rhynchosporium secalis (Oudem.) J.J. Davis) is characterized by a high level of variability, which leads to the emergence of new pathotypes and the loss of resistance of a number of cultivars. Most barley cultivars recommended for cultivation are highly affected by the pathogen. The aim of the study was to find new donors of effective barley resistance genes to R. commune.Materials and methods. Resistance to the fungus was tested in 99 accessions of barley landraces from 18 countries under laboratory and field conditions. The experiments employed isolates and clones of R. commune isolated from plants collected in Leningrad Province. Plant resistance was scored using point scales. Genetic control of fungal resistance was studied in the selected accessions using hybridological analysis.Results and conclusions. We identified 3 accessions of barley landraces, which retained high resistance to the fungus for six years of study in the field under inoculation with different populations of R. commune. Accessions k-31504 (Macedonia), k-31505 (Ethiopia) and k-31503 (India) are protected by R. commune resistance genes, which differ from each other, are not allelic to the previously identified effective Rrs9 gene, and manifest themselves throughout all stages of barley ontogenesis. Each of accessions k-31504 and k-31505 incorporates 2 recessive pathogen resistance genes; k-31503 carries 3 recessive resistance genes.